Effects of bile acids and fatty acids on cell signalling in human colorectal cancer cells - Shah, Syed Ahmad (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2005)
Colorectal cancer is a multifactorial disease. The interplay between genetic and environmental factors leads to the development of CRC. There have been great advancements in the knowledge of genetic alterations leading to CRC and adenoma- carcinoma sequence with corresponding histopathological changes has clearly been defined. The genetic mutations in the hereditary forms of colon cancer can now be analysed by genetic testing in individuals at risk but vast majority of CRC are sporadic in nature with no clear genetic association.
Keywords: Clinical Medicine, Ph.D.; Ph.D. Trinity College Dublin